Bees of the subgenus Allocoelioxys Tkalcu of the genus Coelioxys Latreille (Hymenoptera: Apoidea: Megachilidae) from the Russian Far East - Proshchalykin, Maxim Yu.; Lelej, Arkady S. (Zootaxa, 2004)
Coelioxys (Allocoelioxys) manchurica sp. nov. is described and illustrated from the Russian Far East (Primorskii krai). Coelioxys (A.) afra Lepeletier 1841 is newly recorded from the Russian Far East. A key is given for the females of both species from this area.